Review: Obesity and COVID-19: A Detrimental Intersection - Gammone, Maria Alessandra; D’Orazio, Nicolantonio (Frontiers in Endocrinology, 2021)
Overall, obesity has recently been established as an independent risk factor for critical illness and major severity in patients with coronavirus disease 2019 (COVID-19). The role of fat distribution, especially visceral fat (which is often associated with metabolic abnormalities), remains unclear. The adipose tissue represents a direct source of cytokines; it can mediate the deleterious consequences of systemic inflammation. Obesity and metabolic disorders are closely linked to chronic systemic inflammation leading to a significant increase of visceral fat amount and to a proinflammatory phenotypic shift of this fat storage. This review aims to analyze the interrelation between obesity and COVID-19 severity, as well as the cellular key players and molecular mechanisms involved in adipose inflammation, investigating if adipose tissue can constitute a reservoir for viral spread, and contribute to immune activation and cytokine amplification. Targeting the underlying molecular mechanisms and the altered production of adipokines from adipose tissue may have therapeutic potential in the management of obesity-related complications in COVID-19 patients.